Effect of Continuous Positive Airway Pressure in Phase-I Cardiac Rehabilitation after CABG - Memoona Salal, Sumaiyah Ubaid, Amena Batool, Maria Razzaq, Mashal Rana, Hanifa Suleman, Nadia Anwer, Attaullah Khan Niazi, Muhammad Muneeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Coronary artery bypass surgery is associated with sever alteration of Lung parameters after 1st post-operative day. The purpose of this study to determine The effect of CPAP on, arterial blood gasses, walking time and long term effect on Ejection fraction and quality of life. Objective: To determine the effect of continues positive airway pressure on arterial blood gases, walking time, long term effect on ejection fraction and quality of life in post coronary artery bypass grafting patients. Methods: Randomized control study was conducted in North West General Hospital Peshawar, from July 2019 to December 2019. Patients underwent coronary artery bypass grafting were included in cardiac rehabilitation. 60 patients were randomly divided into two groups with equal half’s. Experimental group received exercises with continues positive airway pressure (CPAP) and control group received only exercise. PAP was applied 20 minutes prior to exercise and ABG’s test and Vitals were recorded after 5minutes of exercise. Walking time was observed by 6MWT on last day of hospital discharge. Ejection fraction was observed by Echo and quality of life by SF12 questionnaire after four weeks. Results: mean age in control group was (55.27±8.80) and in experimental group was (4.70±1.535). Mean and standard deviation of post Echo in experimental group was 48.30±1.493 and control group was 46.17±1.191. Both groups showed significant difference P value less than 0.05 in arterial blood gases PH, HCO3, and PCO2. PO2 showed significant difference only in experimental group. Both groups showed statistically significant difference for 6 MWT. Mean of quality of life in experimental group was 37.4±5.062 and in control was 36.54±4.46. Conclusion: it is concluded that the use of CPAP in post CABG patients have effective outcome in arterial blood gases, walking time, ejection fraction and in quality of life. Keywords: Continuous Positive Airway Pressure, Coronary artery bypass graft surgery, Inpatients rehabilitations.